Dielectric Waveguide for Composite Materials - Fawaz, Nabeil I. (Iraqi Journal of Physics, 2011)
The Maxwell equations have been formulated for a composite slab waveguide at x-band wave propagation. The eigenvalues of the system equations are obtained by using MATLAB program. These eigenvalues are used to obtain the wave propagation constant and a number of modes inside the slabs. A good correspondence was seen between the number of modes and the cut off thickness. The parameter that affects the performance of waveguide is the slab thickness. The propagation constant is usually adopted to characterize this type of waveguide and show how the cutoff frequency of the mode in the slab is increased dramatically by decreasing the frequency. Our study focused on lower modes, the results for the transmission coefficient are then used to study the propagation properties of the guided modes in waveguides. Characteristic equations, solutions for TE (transverse electric) modes are presented. Numerical results for the propagation constant and field distributions of several lower-order modes are presented. By finding the exact transmission coefficient of lower mode of a plane wave incident at a normal incidence on composite slabs, the propagation properties of guided modes in planar slab were studied. It is important to find suitable materials for the transmitting and receiving of microwave frequencies and useful for designing a waveguide filter to separate waves of the same frequency but with different transmission modes.